Effects of the COVID-19 pandemic: new patterns of consumer behavior - E. Karpunina; N. Gubernatorova; T. Sobolevskaya (Вестник Северо-Кавказского федерального университета)
The purpose of the study is to conduct a comparative analysis of the Russian consumption model in the pre-coronavirus period and in the conditions of a pandemic to identify new patterns of consumer behavior, as well as to substantiate the vector of transformation of enterprises’ activities in accordance with the changes that have occurred. The scientific novelty consists in the study of the peculiarities of consumer behavior of Russians, in assessing its changes under the influence of the effects of the pandemic, as well as in justifying measures to reduce the time of adaptation of producers to new behavioral patterns. The article analyzes the structure of household consumption in Russia in the period 2014–2019, and systematizes the features of consumer behavior of the Russian population in the pre-coronavirus period. The effects of the pandemic that influenced the behavior of the Russian consumer are determined. New patterns that determine the nature of consumer behavior of Russians during the pandemic are systematized. It is proved that changes in consumer behavior should be reflected in the production and marketing activities of enterprises. Measures are proposed to ensure maximum efficiency of manufacturers’ adaptation to the changed conditions. The role of the state in overcoming the effects of the pandemic is determined, and institutional and organizational measures are proposed to optimize the ”rules of the game» in the market.